Working Memory Capacity and Dual-Task Interference in Following Instructions - Mohamad Azhari, Abu Bakar; Kartini, Abd Ghani; Norehan, Zulkiply (Human Resource Management Academic Research Society (HRMARS), 2025)
This study employed a dual-task approach to examine the effects of working memory capacity (WMC) on following spoken and written instructions. The participants comprised 26 individuals with high WMC and 26 with low WMC. They completed two types of instruction tasks under interference conditions: spoken instructions paired with an articulatory suppression task, and written instructions paired with a tapping task. In the spoken condition, recall was verbal, whereas in the written condition, recall was action. The results revealed significant main effects of both WMC and dual-task interference on instruction-following performance, as measured by total correct recall. Moreover, a significant interaction between WMC and dual-task interference was found, indicating that interference impaired working memory performance and reduced recall accuracy. Performance was most affected in the verbal recall of spoken instructions with articulatory suppression, especially in the low WMC group.